2020
DOI: 10.3390/su12072788
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Sustainable Apparel and Sportswear Consumption: A Segmented Kano Perspective

Abstract: The steady increase of sustainable consumer behavior leads companies to strengthen their efforts to become socially and ecologically more sustainable. Particularly in the clothing and footwear industry, more and more companies are aware of their need to fundamentally adapt the way they create value. Sustainability offerings are developed, e.g., usage of upcycled materials (e.g., ocean plastic), circular business models (e.g., decomposition of returned products into components for new ones), as well as adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 80 publications
0
28
0
1
Order By: Relevance
“…Research on beaches has shown that coastline plastic waste in 192 countries in 2010 amounted to between 4.8 and 12.7 million metric tons [6]. This waste threatens marine organisms [7] and has led to many demands to restrict plastic use and reshape behavior at the consumer level [8]. Recycling has increased in developed countries since 2006 [1] and offers a partial solution.…”
Section: Introductionmentioning
confidence: 99%
“…Research on beaches has shown that coastline plastic waste in 192 countries in 2010 amounted to between 4.8 and 12.7 million metric tons [6]. This waste threatens marine organisms [7] and has led to many demands to restrict plastic use and reshape behavior at the consumer level [8]. Recycling has increased in developed countries since 2006 [1] and offers a partial solution.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, consumers, and particularly women consumers, have become more concerned with the issues of environmentalism and sustainability. Research has shown that women, more than men, value the environment and are more likely to engage in environmentally friendly behavior (Arora-Jonsson, 2011;Baier et al, 2020). Other research has emphasized the growing popularity of sustainability in consumers' choices when buying activewear.…”
Section: Feminist Readings Of Activewearmentioning
confidence: 99%
“…Moreover, product storytelling "narrative" and the institutional theory and customer behaviour [80] were discussed. Hence, a diverse range of case studies was seen in several articles [81][82][83][84][85][86][87][88].…”
Section: Trends Of Research Studies and Topicsmentioning
confidence: 99%
“…Some sustainable concepts are perceived as adding value [92]. The studies recognised increasing awareness of sustainability in general [84,92,103], growing trends such as the sharing economy in terms of collaborative consumption [95], and more and more awareness of companies in the fashion industry realising the need for sustainable offers [88,100]. Nevertheless, risks and losses were also perceived, as discussed below.…”
Section: Awareness Of Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation